(untitled) (Research, Society and Development, 2022)
Introduction: Given its magnitude and scope, violence against women, constituted as a public health problem, requires specialized and quality assistance, offered by an integrated and articulated network, with care guided by technologies and management tools. Objective: To systematize the prevalence and incidence of physical violence in adult women in health services in Latin America. Method: This is a systematic literature review protocol guided by the Joanna Briggs Institute for Systematic reviews of prevalence and incidence, by searching the LILACS, MEDLINE and Web of Science databases, as well as, the gray literature, in order to answer the guiding question: "What is the prevalence and incidence of physical violence in adult women seen in health services in Latin America?" The review will elucidate specifically, the following questions: Which women (race / color / age / religion (housing) / education) were most victims of violence? Which body segments were most affected? What is the protocol of care for women victims of violence? What is the referral flow to the health services for women victims of violence? To this end, the process of developing this protocol will follow the following steps: review question, inclusion/exclusion criteria, research strategy, selection of studies, data extraction, data synthesis, and evaluation of methodological quality.